Conservative Management of Anterior Abdominal Stab Wounds - Seyed Vahid Hosseini (Shiraz University of Medical Sciences, 2015)
Background Suturing quality and reducing its complications and resulting infection have always been a major concern of surgeons. Many of them have prohibited applying polyfilament and absorbable suturing materials. Objectives In this study, we compared skin wound infection rate and other complications in two groups of post appendectomy patients whom were treated with two types of suturing materials - conventionally used Nylon and absorbable braided polyglactin (Vicryl) - and wound healing, existence of complication and recovery course of treated patients were surveyed. Patients and Methods A total of 130 patients who underwent appendectomy were divided into two groups of 645 members, each. Patients in group A had their incisions closed by separate sutures (mattress method) by vicryl, while patients in group B had their surgical incisions were closed in the same method, by nylon sutures. Any signs and symptoms of surgical site wound infection like inappropriate pain, redness, discharge, bulging, and unhealing wound were checked during hospital stay and on the 7th - 9th day postoperatively. Results The postsurgical complication and infections rates were similar between the two groups. Conclusions Vicryl sutures can safely be used for skin and subcutaneous wound suturing even when our surgery site is not ideally clean.